“Redes de sensores inalámbricas para el monitoreo del consumo energético empleando servicios en redes ad-hoc e iot”. - Pacheco Zamora, José Andrés (2017)
The present research project is based on implementing a network of wireless sensors for the monitoring of energy consumption. Using services in networks Ad-Hoc and Internet of Things, This network consists of a 2-node router, which has been sent to the effective values of the voltage and amperage detected by its integrated sensors; These devices are connected through the ZigBee2 protocol (IEEE 802.15.4) with a coordinating node (base station). In addition, connected to a telemetry server, which is connected to the Ad-Hoc network, it also allows access to the information on the part of the users through a web interface. Finally, the network was implemented in the offices of the company Alfanet Sucursal Quevedo, for the collection of data referring to the consumption made by different Telecommunications equipment provided by the company. Keywords: Networks, Sensors, Wireless, Telemetry, Ad-hoc, IoT, Internet of Things, Mobile Wireless Networks, Wireless Sensor Networks, ZigBee.